2012
DOI: 10.1186/2191-2858-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled green synthesis of silver nanoparticles mediated by gum ghatti (Anogeissus latifolia) and its biological activity

Abstract: BackgroundGum ghatti is a proteinaceous edible, exudate tree gum of India and is also used in traditional medicine. A facile and ecofriendly green method has been developed for the synthesis of silver nanoparticles from silver nitrate using gum ghatti (Anogeissus latifolia) as a reducing and stabilizing agent. The influence of concentration of gum and reaction time on the synthesis of nanoparticles was studied. UV–visible spectroscopy, transmission electron microscopy and X-ray diffraction analytical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(78 citation statements)
references
References 24 publications
6
72
0
Order By: Relevance
“…This is the first time exciting report that microbe-mediated synthesis of nanoparticles was carried out from Streptomyces sp. by hydrothermal autoclaving process in microbial system as compared with the previous report synthesized from plant gum ghatti Anogeissus latifolia [11]. In UV-Visible spectra a strong peak of SPR band with a maximum at 410 nm (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…This is the first time exciting report that microbe-mediated synthesis of nanoparticles was carried out from Streptomyces sp. by hydrothermal autoclaving process in microbial system as compared with the previous report synthesized from plant gum ghatti Anogeissus latifolia [11]. In UV-Visible spectra a strong peak of SPR band with a maximum at 410 nm (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…This strongly suggests that the reduction of Ag was carried out by some hydroxyl groups that get oxidized at the expense of Ag because Ag is reduced. 54 …”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Recently, Kora et al demonstrated that functional groups, such as COOH and OH from gum ghatti, have the ability to reduce silver nanoparticles. 23 Temozolomide was conjugated with gold nanoparticles in order to obtain the GNP-L-aspartate-TMZ delivery vector of interest. The morphological, optical, and structural characteristics of the vector were then investigated by transmission electron microscopy (TEM), along with Fourier transform infrared spectroscopy (FTIR), and x-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%